Checklist of species of Stratiodrilus Haswell, 1900 (Annelida: Histriobdellidae), and new host records from Southern Brazil - Da Silva Rosa, Jheimison Junior; Marçal, Ingrid Costa; Teixeira, Gustavo Monteiro; Aguiar, Aline (Zootaxa, 2018)
Species of Stratiodrilus are ectocommensals of freshwater decapod crustaceans, and the genus is also the most speciose within the family Histriobdellidae. However, a global review of the species of Stratiodrilus and their hosts has not been performed in nearly two decades. Based new field collections in Brazil and a literature search, we present a list of Stratiodrilus species and their hosts. We searched for host and occurrence records in papers of species descriptions, review papers and specialized databases. Forty-one host records were summarized worldwide. All host taxa were freshwater decapod crustaceans belonging to Aegla, Astacoides, Astacopsis, Cherax, Parastacus, Samastacus, and Trichodactylus. In addition, we report four new host records for Stratiodrilus circensis, and found Aegla lata as the northernmost host record for this polychaete species. Stratiodrilus circensis also had the largest number of different host species. The greatest species richness of Stratiodrilus is found in the Neotropical region, although members of this genus are also found in Australia and Madagascar associated with crayfishes. Aegla was the most reported host genus associated with species of Stratiodrilus. We provide an updated list to the known species of Stratiodrilus and also discuss the distribution of these histriobdellids.